Penerapan Instrumen Penilaian Ranah Afektif dalam Hasil Belajar Kurikulum 2013 di SDN Cipaeh - Akbar, Ahmad Alvinda; Wijaya, Arman; Ayanih, Ayanih; Humaerah, Humaerah; Magdalena, Ina (Lembaga Yasin AlSys, 2023)
This research was carried out with the aim of knowing the application of affective domain assessment instruments in the learning outcomes of the 2013 curriculum at SDN Cipaeh. In addition, this study also analyzed the effectiveness of affective assessment instruments used by teachers in assessing students' attitudes and motivation levels. The results of this study are expected to provide valuable input for the school in improving the quality of learning and the assessment process. This study used observation and questionnaire methods with a Likert scale of 1-5. Data will be collected through class observations, interviews with teachers and students, as well as analysis of related documents. In identifying and analyzing affective domain assessment instruments, researchers will refer to the latest educational psychology theories that are relevant to this research.